Implementasi Kepemimpinan Demokratis Dalam Pemberdayaan Guru Penggerak Di SMP Negeri 3 Welahan - Fauzi, Noor Ali; Bunyamin, Bunyamin; Murniati, Ngurah Ayu Nyoman (Cetta: Jurnal Ilmu Pendidikan, 2025)
SMP Negeri 3 is an outstanding school, one of its achievements is recorded as the school that produces the most leading teachers in Welahan sub-district in 2024-2025. In an effort to further empower the potential of leading teachers for school progress, democratic leadership of the principal is needed who is able to empower the potential of these teachers. This study aims to describe the implementation of democratic leadership of the principal in empowering teachers at SMP Negeri 3 Welahan. The sub-focus of the study includes participatory decision-making, and management and facilitation, Qualitative research methods with case study types in the SMP Negeri 3 Welahan area. Data collection techniques use observation, interviews and documentation. The research design begins with pre-field, field tests, and data analysis. Data analysis techniques include data collection, data condensation, data presentation and drawing conclusions. The results of the study show that the principal applies participatory decision-making by involving teachers in various discussion forums, coordination meetings, and open deliberations. The principal prepares a teacher empowerment program through needs analysis, develops alternative work procedures through group discussions and manages resources by supporting self-development communities that are carried out according to school needs. The research recommendations are aimed at related parties in developing evaluation mechanisms for teacher empowerment programs on real learning quality with measurable indicators.